Overview of Radiological Images of Chest X-ray s of Patients with Tuberculosis at BARI General Hospital, Palembang, Indonesia - Agustina, Dessy (Sriwijaya Journal of Radiology and Imaging Research, 2023)
Introduction: Tuberculosis (TB) is a chronic and contagious infectious disease that can attack almost all organs of the human body, especially the lungs, caused by the bacterium Mycobacterium Tuberculosis. Chest X-ray is a fast imaging technique and one of the main tools that have high sensitivity for diagnosing pul monary TB. This study aimed to find out more about the overview of radiological images of chest X-rays of patients with tuberculosis at BARI General Hospital , Palembang, Indonesia. Methods: This study is a descriptive observational study. A total of 50 research subjects participated in this study. The radiological images of the chest X-rays are presented in the form of grouping, namel y the presence of infiltrates, consolidation, fibrosis, cavities, and effusions. In addition, observations were made on the location of the emergence of va rious abnormalities on the radiological image of the chest X-rays in a descriptive way. Results: This study showed that the majority of study subjects had to infiltrate radiological features, and the majority of study subjects had le sions at the apex of the superior lobe. Conclusion: The radiological images of the chest X-rays in TB patients show the presence of infiltrate, consoli dation, fibrosis, effusion, and cavity lesions, where the lesions are in line with the progressivity of TB.